How Teachers Feel Good: The Role of Teachers' Mindfulness, Self-efficacy and Implicit Attitudes towards Ethnic Minority Students in Their Feelings of Burnout - Sara Costa; Sabine Glock; Sabine Pirchio (LED Edizioni Universitarie, 2024)
COME GLI INSEGNANTI SI SENTONO BENE: IL RUOLO DELLA MINDFULNESS, DELL'AUTOEFFICACIA E DEGLI ATTEGGIAMENTI IMPLICITI DEGLI INSEGNANTI VERSO GLI STUDENTI CON BACKGROUND ETNICO MINORITARIO, NELLA LORO SENSAZIONE DI BURNOUT Abstract Burnout is a complex syndrome, and decades of research have established that teaching is a stressful profession. New evidence suggests that teachers' ethnic prejudice and attitudes might help to explain teachers' burnout related to ethnic diversity. On the other hand, factors such as self-efficacy and mindfulness are known to play a protective role for burnout, but to date it is not known how they are related to implicit attitudes and prejudice as well. In this study, we aim to provide a deeper understanding of the mechanism underlying the development of burnout in teachers and pre-service teachers, investigating the role of ethnic prejudice, implicit ethnic attitudes, perceived self-efficacy and mindfulness. Our results show that self-efficacy and mindfulness are negatively correlated with teacher burnout and that mindfulness moderates the relationship between implicit ethnic attitudes and burnout. Theoretical and practical implications of these findings are discussed.